Tsukamurella tyrosinosolvens - An unusual case report of bacteremic pneumonia after lung transplantation - Dromer Claire; Nguyen Thi; Peuchant Olivia; Degrange Sébastien; Ménard Armelle; Maugein Jeanne (BMC, 2009)
Abstract Background Lung transplant recipients have an increased risk for actinomycetales infection secondary to immunosuppressive regimen. Case presentation A case of pulmonary infection with bacteremia due to Tsukamurella tyrosinosolvens in a 54-year old man who underwent a double lung transplantation four years previously is presented. Conclusion The identification by conventional biochemical assays was unsuccessful and hsp gene sequencing was used to identify Tsukamurella tyrosinosolvens.